Mongolia : Report on the Observance of Standards and Codes; Data Module, Response by the Authorities, and Detailed Assessment Using the Data Quality Assessment Framework (DQAF). - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Mongolia meets many of the General Data Dissemination System (GDDS) recommendations for coverage, periodicity, and timeliness. The major exceptions include the following: the incomplete coverage of the international investment position; the nonavailability of a primary commodity, agricultural, or other relevant production index; the producer price index; wages and earnings; nonguaranteed private external debt; as well as the nondissemination of data on central government debt and government-guaranteed debt; public and publicly guaranteed external debt and debt service schedule; gross official reserves; and reserve-related liabilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet